2016
DOI: 10.1007/s10707-016-0254-1
|View full text |Cite
|
Sign up to set email alerts
|

On discovering co-location patterns in datasets: a case study of pollutants and child cancers

Abstract: We intend to identify relationships between cancer cases and pollutant emissions by proposing a novel co-location mining algorithm. In this context, we specifically attempt to understand whether there is a relationship between the location of a child diagnosed with cancer with any chemical combinations emitted from various facilities in that particular location. Colocation pattern mining intends to detect sets of spatial features frequently located in close proximity to each other. Most of the previous works i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 34 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…20,21 Having more than one patient with CRC in family, having under 60 years old patient in family, 21,22 and female sex of CRC patients in family are associated with the prevalence of advanced colonic neoplasms in participants. Smoking, also, was recognized as an important factor for advanced colonic neoplasms in male clusters and this result also admitted in study of Lee et al and Li et al 23,24 Furthermore, obesity was cited by Liu et al 25 as a risk factor and this study achieved reported this factor as well. The effect of obesity on the incidence of CRC was mentioned in study results of Bardou et al 10 Many people who anticipated to have cancer were under 50 years old and it seems that age of presenting cancer is declining, and this result admitted in paper of Smith et al 26 However, it has been shown in few clusters that old people are on the verge of cancer.…”
Section: Discussionsupporting
confidence: 75%
“…20,21 Having more than one patient with CRC in family, having under 60 years old patient in family, 21,22 and female sex of CRC patients in family are associated with the prevalence of advanced colonic neoplasms in participants. Smoking, also, was recognized as an important factor for advanced colonic neoplasms in male clusters and this result also admitted in study of Lee et al and Li et al 23,24 Furthermore, obesity was cited by Liu et al 25 as a risk factor and this study achieved reported this factor as well. The effect of obesity on the incidence of CRC was mentioned in study results of Bardou et al 10 Many people who anticipated to have cancer were under 50 years old and it seems that age of presenting cancer is declining, and this result admitted in paper of Smith et al 26 However, it has been shown in few clusters that old people are on the verge of cancer.…”
Section: Discussionsupporting
confidence: 75%
“…As for airborne pollutants, a total of 136 chemicals from the industry activities were registered in NPRI during the study period. The location of the emission sites, the average emission amount, and the predominant wind (direction and speed) at each site were used to create a dispersion region for the chemicals [23]. A pregnant woman was considered exposed to a chemical if her activity area (a 5 km radius from the center of the postal code of her residence) overlapped with the dispersion region of the chemical (Fig.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…As an important branch of data mining, spatial colocation pattern mining has been proven to be an effective data mining technique for obtaining profit from spatial data. This technique can be extensively used in many application domains, including location‐based services [1], public safety [2], mobile communication services [3], environmental management [4], disease control and public health [5], social science [6], evolvement [7], and so on.…”
Section: Introductionmentioning
confidence: 99%